2006
DOI: 10.1007/s10765-005-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Instrument for the Measurement of the Thermal Conductivity of Molten Metals. Part I: Instrument’s Description

Abstract: The paper reports the design and construction of a new instrument for the measurement of the thermal conductivity of molten metals and salts. The apparatus is based on the transient hot-wire technique, and it is intended for operation over a wide range of temperatures, from ambient up to 1200 K. The present experimental technique overcomes problems of convection and thermal radiation, and it is demonstrated that it operates in accord with a theoretical model. The uncertainty of the thermal conductivity results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Design (b) is based on the same idea, but here the wire is placed between soft alumina layers which are consequently fired under pressure to become solid [60]. This arrangement worked very well for measurements of the thermal conductivity of molten metals at high temperatures; Peralta-Martinez et al [61] reported such measurements for molten mercury, gallium, tin, and indium up to 750 K. In order to accurately measure the resistance of the wires, electronic bridges were developed rapidly following the advances in electronics and computers.…”
Section: Period From 1971 To Todaymentioning
confidence: 99%
“…Design (b) is based on the same idea, but here the wire is placed between soft alumina layers which are consequently fired under pressure to become solid [60]. This arrangement worked very well for measurements of the thermal conductivity of molten metals at high temperatures; Peralta-Martinez et al [61] reported such measurements for molten mercury, gallium, tin, and indium up to 750 K. In order to accurately measure the resistance of the wires, electronic bridges were developed rapidly following the advances in electronics and computers.…”
Section: Period From 1971 To Todaymentioning
confidence: 99%
“…Of course, the technique cannot be identical but the same methodology was used in the construction of the apparatus: one looks for an accurate description of the experimental method, and then seeks to define or construct an instrument that replicates the theoretical model as nearly as possible [124]. Figure 19 shows the basis of the idea [125].…”
Section: Molten Metalsmentioning
confidence: 99%
“…modeling to describe this heat transfer process. For that purpose, the complete system is divided into a series of meshes that accounts for the fact that there is a mixture of geometry between the circular wire and the rectangular elements, and a finite element model based upon conventional Fourier equations can be built and solved as described elsewhere [124,126,127]. It is then possible to predict from assumed values of the thermal conductivity, heat capacity, and density of the wire, the substrate, the molten metal and, if necessary, any interface elements, the temperature history of the wire subject to a transient heat input.…”
Section: Molten Metalsmentioning
confidence: 99%
“…The method has been further refined [2] and used for measurements of the thermal conductivity of liquid mercury, gallium, indium, and tin [3,4]. In principle, the method consists of two main steps.…”
Section: Modified Transient Hot-wire Techniquementioning
confidence: 99%
“…The nature of the temperature rise of the hot-wire allows accurate measurements of the thermal conductivity of the materials surrounding the hot-wire, and a FE implementation of a solution of the heat transfer equations for the sensor/fluid complex is employed to deduce the thermal conductivity of the fluid and the sensor in situ. A detailed description of the method, its background theory and an analysis of the temperature response of the hot-wire have been published elsewhere [2][3][4]. These publications also discuss in detail the importance of radiation and natural convection for this kind of THW technique.…”
Section: Modified Transient Hot-wire Techniquementioning
confidence: 99%